Potential probiotic salami with dietary fiber modulates metabolism and gut microbiota in a human intervention study. (March 2020) - Pérez-Burillo, S.; Pastoriza, S.; Gironés, A.; Avellaneda, A.; Pilar Francino, M.; Rufián-Henares, J.A.
Graphical abstract: Highlights: Neither anthropometric measurements nor plasmatic lipids changed after salami intake. Salami enriched with dietary fiber led to higher abundances of butyrate producing gut microbes. Salami enriched with dietary fiber improves butyric acid production by gut microbiota. Inflammatory markers, TNF-α and CRP decreased while plasmatic antioxidant capacity increased. Abstract: A human intervention in 24 healthy volunteers was performed to test the potential health benefits of a fermented salami with a probiotic Lactobacillus rhamnosus HN001 and added citrus fiber. Anthropometric measurements and blood biochemistry did not show any significant differences between pre- and post-intervention during 4 weeks with a daily intake of 30 g of salami, neither with regular salami (control group) nor with reformulated salami (intervention group). However, the inflammatory markers CRP and TNFα decreased significantly after intervention, suggesting a less inflammatory environment after reformulated salami consumption. Antioxidant plasmatic markers also improved within the intervention group. Butyrate production was significantly increased after reformulated salami consumption. Gut microbiota community structure, however, was not significantly shaped by neither regular nor reformulated salami. After the intervention with probiotic salami, L. rhamnosus was detected by quantitative polymerase chain reaction (qPCR) in all samples of the intervention group but not in the control group, showing probiotic effect.